GIGECONOMY, STRENGTHENING HUMAN RESOURCES AND DIGITAL COMMUNICATION STRATEGIES TOWARDS DECENT WORK IN SUPPORTING SUSTAINABLE DEVELOPMENT (SDGs 8) IN MATARAM CITY - Ni Luh Putu Anom Pancawati; Ida Ayu Nyoman Sutriani; Ni Nyoman Suli Asmara Yanti; Edy Chandra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
GIG Economyhave new flexible job opportunities especially for women who have dual responsibilities in society.This study aims to examine the influence of the GIG Economy, Human Resource Development, and Digital Communication Strategy on Decent Work in Supporting Sustainable Development (SDGs 8) in Mataram City. Using a sample of 100 female workers respondents who work in the digitalization sector (remote working). The independent variables are the GIG Economy, Human Resource Development, and Digital Communication Strategy with the dependent variable being Decent Work. This type of causal quantitative research uses multiple linear regression analysis as the data processing method. The sampling method is purposive sampling with accidental sampling as the sampling technique. The data collection method uses a questionnaire. The research instrument is tested with validity and reliability tests. Before analyzing the research data, a classical assumption test is first carried out, followed by a t-test and an F-test for drawing conclusions. The results of the study state that the GIG Economy, Human Resource Development, and Digital Communication Strategy have a positive and significant effect, both partially and simultaneously, on Decent Work. This means that job opportunities through the GIG Economy, improving the quality of skills and abilities in utilizing digital platforms collectively become an effective strategy in encouraging the realization of decent work for female workers and directly supporting the successful achievement of SDGs 8 in Mataram City.